2018
DOI: 10.1177/0898264318814997
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Long-Term Improvement in Subjective Everyday Memory Following a Memory Group Program for Older Adults

Abstract: Objective: The present study aimed to examine predictors of improvement in subjective everyday memory ability 5 years following participation in a group cognitive-behavioral memory intervention for community-living older adults, the La Trobe and Caulfield Hospital (LaTCH) Memory Group program. Method: Participants were 61 healthy older adults and data were analyzed using one-way repeated measures analysis of variance (ANOVA), hierarchical regression, and moderator analyses. Results: Although the group as a who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(98 reference statements)
1
1
0
Order By: Relevance
“…Importantly, attrition did not differ between those with high and low levels of SCD, and thus it is unlikely to impact the observed interaction of declining habitual PM for people with SCD, compared with relative stability in people without SCD. Overall, the level of attrition within the current study was in line with studies of a similar nature, where retention rates at 5 years are often reported at 50% (Matthews et al, 2020). Therefore, the sample size can be considered adequate within this follow-up study.…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, attrition did not differ between those with high and low levels of SCD, and thus it is unlikely to impact the observed interaction of declining habitual PM for people with SCD, compared with relative stability in people without SCD. Overall, the level of attrition within the current study was in line with studies of a similar nature, where retention rates at 5 years are often reported at 50% (Matthews et al, 2020). Therefore, the sample size can be considered adequate within this follow-up study.…”
Section: Discussionsupporting
confidence: 86%
“…Subjective memory complaints (SMC) reflect an individual’s dissatisfaction with his or her memory function, which is common in community-dwelling older adults ( Matthews et al, 2020 ; Mitchell et al, 2014 ). SMC appears to be associated with poor outcomes, including reduced social participation, increased emotional symptoms (e.g., depression and anxiety), and low quality of life ( Mogle et al, 2017 ; Montejo et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%